2024
DOI: 10.1039/d3bm01735d
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of gefitinib loaded nanoparticles for effectively inhibiting prostate cancer progression

Zhi Xiong,
Tong Tong,
Zhaoxiang Xie
et al.

Abstract: Androgen deprivation therapy is administered to suppress the growth of prostate cancer (PCa). However, some cells continue to proliferate independently of hormones, leading to the development of castration-resistant prostate cancer...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…54 According to the research by Xiong et al, the use of gefitinib-loaded poly(D,L-lactide-co-glycolide) acid nanoparticles demonstrated significant effectiveness in preventing the advancement of prostate cancer. 55 In a separate research project, it was discovered that the utilization of poly Lglutamic acid (PGA)-loaded anti-insulin growth factor 1 receptor antibody (known as AVE1642) effectively suppressed the advancement of tumors in an orthotopic prostate cancer mouse model. 56 The drug carrier 8P4 NPs used in this study is an L-phenylalanine polymer with good biocompatibility and biodegradability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…54 According to the research by Xiong et al, the use of gefitinib-loaded poly(D,L-lactide-co-glycolide) acid nanoparticles demonstrated significant effectiveness in preventing the advancement of prostate cancer. 55 In a separate research project, it was discovered that the utilization of poly Lglutamic acid (PGA)-loaded anti-insulin growth factor 1 receptor antibody (known as AVE1642) effectively suppressed the advancement of tumors in an orthotopic prostate cancer mouse model. 56 The drug carrier 8P4 NPs used in this study is an L-phenylalanine polymer with good biocompatibility and biodegradability.…”
Section: Discussionmentioning
confidence: 99%
“…Shu et al endeavored to attach hyaluronic acid (HA) to a zeolite imidazolate backbone material to conduct MRI imaging of PC-3 cells in human prostate cancer . According to the research by Xiong et al, the use of gefitinib-loaded poly­( d , l -lactide- co -glycolide) acid nanoparticles demonstrated significant effectiveness in preventing the advancement of prostate cancer . In a separate research project, it was discovered that the utilization of poly l -glutamic acid (PGA)-loaded anti-insulin growth factor 1 receptor antibody (known as AVE1642) effectively suppressed the advancement of tumors in an orthotopic prostate cancer mouse model .…”
Section: Discussionmentioning
confidence: 99%